2018
DOI: 10.1123/kr.2018-0037
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Teaching and Learning Strategies in Kinesiology

Abstract: Although the use of active-learning strategies in the classroom is effective, it is underutilized due to resistance to change from the traditional classroom, a limited evidence base for optimizing engaged learning, and limited support for faculty to overhaul their course structure. Despite these barriers, engaged learning is highly relevant, as the expected job skills of graduates continue to grow and are biased away from rote memorization and toward critical thinking and communication skills. The STEM (scienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Usmeritev področja kineziologije v prihodnosti narekuje prilagodljivost študijske strukture s ciljem umeščanja na obstoječi trg dela kot tudi večjimi možnostmi zaposlovanja (Ennis, 2010). Zaradi hitrega razvoja področja kineziologije in njene umeščenosti v več družbenih področij (izobraževanje, šport, krepitev zdravja, prosti čas, turizem in druga) pa je potrebna tudi nenehna skrb za prilagajanje metod poučevanja in spodbujanja aktivnih učnih strategij med študenti kineziologije (Bodary in Melissa Gross, 2018).…”
Section: Preference Za Področje Delaunclassified
“…Usmeritev področja kineziologije v prihodnosti narekuje prilagodljivost študijske strukture s ciljem umeščanja na obstoječi trg dela kot tudi večjimi možnostmi zaposlovanja (Ennis, 2010). Zaradi hitrega razvoja področja kineziologije in njene umeščenosti v več družbenih področij (izobraževanje, šport, krepitev zdravja, prosti čas, turizem in druga) pa je potrebna tudi nenehna skrb za prilagajanje metod poučevanja in spodbujanja aktivnih učnih strategij med študenti kineziologije (Bodary in Melissa Gross, 2018).…”
Section: Preference Za Področje Delaunclassified
“…Faculty also task students with being actively engaged outside of class so that learning within the classroom can be more active. The use of flipped classrooms (Killian & Woods, 2018;Lumpkin & Achen, 2015), blended learning (Bodary & Gross, 2018), and team-based learning (Parr, 2013) are all pedagogical strategies that require students to be actively involved in the construction of their own knowledge both in and out of classrooms.…”
Section: Active Learningmentioning
confidence: 99%
“…In prior studies, both individual assignment grades and final grades were shown to be improved within an ALC compared with a traditional, lecture-based class (Brooks & Solheim, 2014;Freeman et al, 2014). Active learning can also address the demand for nonknowledge-based abilities, sometimes referred to as soft skills (Bodary & Gross, 2018). By engaging with peers and having to clearly articulate one's own ideas, students are given opportunities to strengthen their abilities of critical thinking and working in teams (Bodary & Gross, 2018).…”
Section: Active Learningmentioning
confidence: 99%
See 1 more Smart Citation